A new species-group of Chrysura Dahlbom, 1845 (Hymenoptera: Chrysididae), with description of Ch. baiocchii sp. nov. from Iran - Rosa, Paolo; Lotfalizadeh, Hosseinali (Zootaxa, 2013)
Chrysura baiocchii Rosa sp. nov. is described from Iran. Diagnosis of the new species-group Ch. baiocchii and discussions on Ch. radians group and Ch. genalis subgroup are given.